Study on the determination of ¹⁰B/¹¹B isotope ratio in water samples by isotope dilution – inductively coupled plasma mass spectrometry (ID-ICPMS) - Nguyen Thi, Kim Dung; Nguyen, Thi Lien (Nuclear Science and Technology, 2017)
The determination of 10B/11B isotope ratio and boron concentration in various water samples using isotope dilution technique with inductively coupled plasma mass spectrometry (ICPMS) was studied. The interferences on precision and accuracy in isotopic ratio determination by ICPMS such as memory effects, dead time, spectral overlap of 12C were investigated for the selection of optimum conditions. By the addition of certain amounts of enriched 10B into samples, the 10B/11B ratio was determined through ICP-MS signal of 10B and 11B. The detection limit for 10B and 11B was experimentally obtained as 0.26 µg/L and 0.92 µg/L, respectively. The ratios of 10B/11B in measured water samples varied in the ranged between 0.1905 and 0.2484 for different matrices. This method has been then applied for the determination of boron isotopic ratio in VVER-1000 reactor-type simulated primary coolant water and in some environmental water samples.